2006
DOI: 10.2298/gsf0694197m
|View full text |Cite
|
Sign up to set email alerts
|

Effect of host plant on gypsy moth diet and biological efficacy of Btk preparations

Abstract: The effect of two host plants, Turkey oak (Quercus cerris L) and black poplar (Populus nigra L) on gypsy moth (Lymantria dispar L) development was researched. The effect of host plant was determined based on the parameters which characterize the diet, growth and efficacy of conversion of ingested food of the third instar caterpillars. Along with the effect on development, the effect of host plant on the efficacy of biological preparation based on the bacterium Bacillus thuringiensis var. kurstaki in gypsy moth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 5 publications
1
4
0
Order By: Relevance
“…Saponins are reported as extremely poisonous compounds that cause hemolysis of blood (Kar, 2007). They are Plant secondary metabolites that are known to be effective repellents for a number of harmful insects (Milanovic, 2006;Erturk et al, 2006 andShields et al, 2006) which is in line with our results. Pelah et al (2002) studied the larvicidal activity of commercial bark saponin extract from Quillaja saponaria on 3rd-4th instar larvae of Aedes aegypti and Culex pipiens.…”
Section: Discussionsupporting
confidence: 92%
“…Saponins are reported as extremely poisonous compounds that cause hemolysis of blood (Kar, 2007). They are Plant secondary metabolites that are known to be effective repellents for a number of harmful insects (Milanovic, 2006;Erturk et al, 2006 andShields et al, 2006) which is in line with our results. Pelah et al (2002) studied the larvicidal activity of commercial bark saponin extract from Quillaja saponaria on 3rd-4th instar larvae of Aedes aegypti and Culex pipiens.…”
Section: Discussionsupporting
confidence: 92%
“…According to Shields et al (2006), L. dispar best develops on species belonging to the genus Quercus (Janković, 1958), especially Q. robur, Q. cerris (Milanović, 2006) and/or Q. rubra. Previous research by Gvozdenac et al (2010Gvozdenac et al ( , 2011 has also indicated that L. dispar larvae feed most intensively on Q. robur as their primary host, which was confirmed in this work.…”
Section: Discussionmentioning
confidence: 99%
“…For L. dispar, repellent activity is especially common by plants with high alkaloid contents (Dosktotch, 1980). In recent years, antifeeding effects of various plant extracts have been studied by several authors (Zabel et al, 2002;Milanović, 2006;Kostić, 2008;Gvozdenac et al, 2010Gvozdenac et al, , 2011Pavela, 2010). According to Simmonds (2000), more than 6,250 plants have been tested for different insecticidal activities since 1985, while Parkash and Rao (1997) confirmed that about 870 herbal products with insecticidal or repellent antifeeding effect were used in agriculture.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The abundance, i.e. the population level of the gypsy moth is conditioned by the characteristics of the species, physiological conditions of some instars, as well as by the biotic and abiotic factors, such as weather conditions, type and quality of host plants, pathogens, natural enemies (Milanović et al, 2006;Tabaković-Tošić, 2011, 2012Tabaković-Tošić et al, 2013).…”
Section: Introductionmentioning
confidence: 99%